2010
DOI: 10.1177/0091270010377201
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐Response Modeling of Darbepoetin Alfa in Anemic Patients With Chronic Kidney Disease Not Receiving Dialysis

Abstract: A population pharmacokinetic and pharmacodynamic model (PK/PD) of darbepoetin alfa following intravenous (IV) or subcutaneous (SC) administration in participants with chronic kidney disease (CKD) was developed. Darbepoetin alfa concentrations from 96 CKD participants, who received IV or SC darbepoetin alfa, and Hgb concentration from 332 CKD participants not on dialysis, who received SC doses of darbepoetin alfa, were used to develop the PK/PD model. An open 2-compartment model with sequential zero- and first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 58 publications
(130 reference statements)
4
13
0
Order By: Relevance
“…Several empirical, mechanistic and semimechanistic models have been built to explore the dose–response relationship for epoetin alfa. In the early 1950s, several investigators reported that RBCs exist for a fixed duration of time or life span, which was estimated to be 120 days in healthy subjects, although it might vary in diseased populations such as those with leukemia (71–76 days) or renal impairment, including patients not on hemodialysis (77 days) . In these populations, the shortening of RBC life span may contribute to anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical, mechanistic and semimechanistic models have been built to explore the dose–response relationship for epoetin alfa. In the early 1950s, several investigators reported that RBCs exist for a fixed duration of time or life span, which was estimated to be 120 days in healthy subjects, although it might vary in diseased populations such as those with leukemia (71–76 days) or renal impairment, including patients not on hemodialysis (77 days) . In these populations, the shortening of RBC life span may contribute to anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Krzyzanski reported that as the number of transit compartments in a cytokinetic model increases, this model becomes equivalent to a life span model. A simpler model without a precursor pool was also proposed and uses endogenous erythropoietin ( eEPO) to establish the baseline Hb level.…”
mentioning
confidence: 99%
“…For instance, as the production rate of neutrophils is controlled by the duration of the differentiation and maturation of stem cells and progenitor cells, respectively, drugs affecting directly the proliferation of stem cells will exhibit an effect on neutrophil counts in the circulation with a delay of 4–5 days, which is equivalent to the duration of the differentiation and maturation processes [12]. Similarly, the time to achieve hemoglobin concentrations at steady state following the treatment with erythropoiesis stimulating agents in anemic patients with chronic kidney diseases depends on the lifespan of red blood cells, which is approximately 2–3 months [13]. These two examples illustrate the importance of accounting for the long duration of the physiological processes involved in both the production and elimination of cells in order to adequately characterize the time course of drug response.…”
Section: Introductionmentioning
confidence: 99%
“…Such a sequence of compartments is necessary to account for a delay between exposure of progenitor cells to a therapeutic/ toxic agent and its effect which is typically determined from the blood cells count (maturation) or the time dependent change in the age of a particular cell type (senescence). A sequence of age compartments is the bone structure of more complex pharmacodynamic models of drugs affecting hematopoietic cell populations such as neutrophils [8, 28, 29], red blood cells [13, 3032], and platelets [7, 9]. In these models drug stimulated or inhibited the production of cell precursors or the transfer rate between the age compartments.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 15 years, the use of clinical trial simulation (CTS) in evaluating the selection of dosing regimens that maximize efficacy and minimize toxicity risk has been well documented in the literature . However, there is scarcity of information on utilizing CTS to assess the efficiency of dose titration schemes …”
mentioning
confidence: 99%